The temporal shift of peri-implant microbiota during the biofilm formation and maturation in a canine model. (September 2021) - Jiang, Qiming; Yu, Yi; Xu, Ruogu; Zhang, Zhengchuan; Liang, Chaoan; Sun, Hanyu; Deng, Feilong; Yu, Xiaolin
Abstract: Objectives: Although the mature peri-implant biofilm composition is well studied, there is very little information on the succession of in vivo dental implant colonization. The aim of this study was to characterize the temporal changes and diversity of peri-implant supra-mucosal and sub-mucosal microbiota during the process of the plaque maturation. Materials and methods: Dental implants (n = 25) were placed in the mandible of 3 beagle dogs. Illumina MiSeq sequencing of the hypervariable V3-V4 region of the 16S rRNA gene amplicons was used to characterize the supra/sub-mucosal microbiota in the peri-implant niches at 1day (T1), 7days (T2), 14days (T3), 21days (T4) and 28days (T5) after Phase Ⅱ surgery of the healing abutment placement. QIIME, Mothur, LEfSe and R-package were used for downstream analysis. Results: A total of 1184 operational taxonomic units (OTUs), assigned into 22 phyla, 264 genera and 339 species were identified. In supra-mucosal niches, the alpha parameters of shannon, sobs and chao1 displayed significant differences between T1 and other time-points. However, in sub-mucosal niches, only sobs, chao1, and ace indexes displayed significant differences between T1 and T3, and T1 and T5. Beta-diversity showed statistically significant difference between T1 and T2, T3, T4, T5 within both sub-mucosal and supra-mucosal plaque. The phyla Bacteroidetes, Proteobacteria and Firmicutes were the most dominant phyla of both sub-mucosal and supra-mucosal niches at all time-points and Firmicutes increased during the maturation of peri-implant plaque. At the genus level, Neisseria decreased significantly after T1 suggesting the establishment of an anaerobic microenvironment. A decrease of Porphyromonas during the formation of sub-mucosal microbial community was also detected. Co-occurrence network analysis exhibited a more complicated co-occurrence relationship of bacterial species in the sub-mucosal niches. Fusobacteriu m nucleatum, Filifactor villosus, and some other species may play a crucial role in biofilm maturation. Conclusions: The present results suggested that the development of peri-implant biofilm followed a similar pattern to dental plaque formation. Sub-mucosal biofilm may go through a more complicated procedure of maturation than supra-mucosal biofilm. Highlights: ● Development of peri-implant biofilm is similar to dental plaque formation. ● Maturation of peri-implant biofilm is contrary to peri-implantitis development. ● F. nucleatum, F. villosus and P. sphenisci are keystone taxa in biofilm formation.